Preparation method of pure 1T-phase transition metal chalcogenide

By using N-methylformamide to perform solvothermal reaction in the preparation of 1T phase transition metal chalcogenides, the problem of the inability to obtain pure 1T phase and structural stability in the prior art is solved, and high purity and large layer spacing are achieved 1T phase transition metal chalcogenide improves its performance in catalytic and energy storage applications.

CN119118200APending Publication Date: 2024-12-13SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411276469.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing 1T phase transition metal chalcogenide preparation methods cannot obtain pure 1T phase (100%) and its structural stability is insufficient, resulting in poor performance in catalysis, energy storage and other applications.

Method used

N-methylformamide is used as solvent for solvothermal reaction, and a pure 1T phase transition metal chalcogenide is formed through in situ electron injection and intercalation structure, expanding its layer spacing and increasing the phase transition temperature to stabilize its 1T phase structure.

Benefits of technology

A transition metal chalcogenide with a pure 1T phase (100%) has been achieved, with large layer spacing and excellent physical and chemical stability. It is suitable for high activity, high specific surface area and high stability applications such as supercapacitors and ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118200A_ABST
    Figure CN119118200A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a pure 1T-phase transition metal chalcogenide, which comprises the following steps: (1) adding raw materials for preparing the transition metal chalcogenide into N-methylformamide, and fully stirring to obtain a precursor solution; (2) performing solvothermal reaction on the precursor solution in a reaction kettle; and after the reaction is completed, cleaning and drying the obtained reaction product to obtain the pure 1T-phase transition metal chalcogenide. According to the method, N-methylformamide is adopted as a solvent for solvothermal reaction, the pure 1T-phase transition metal chalcogenide can be prepared, the prepared pure 1T-phase transition metal chalcogenide has large interlayer spacing (about 0.96-1.14 nanometers), and the large interlayer spacing is beneficial to intercalation / deintercalation of atoms, molecules or ions in some physical / chemical reaction processes; meanwhile, due to internal electron enrichment and an intercalation structure, the prepared pure 1T phase transition metal chalcogenide has excellent physical and chemical stability, and the 1T phase structure of the pure 1T phase transition metal chalcogenide has good high-temperature-resistant stability (phase structure transformation does not occur at the temperature of 300 DEG C or below).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing pure 1T phase transition metal chalcogenide. Background Art

[0002] Group VI transition metal chalcogenides, such as MoS 2 , WS 2 、MoSe 2 ,WSe 2 , with a typical graphite-like layered structure (its single layer is composed of two upper and lower S or Se atomic layers and a middle Mo or W atomic layer to form a sandwich structure). Due to its special layered structure, large specific surface area, rich element reserves and other characteristics, the sixth group transition metal sulfide has important applications in friction lubrication, catalytic refining, battery electrodes, photoelectric hydrogen production and many other fields. Rich phase structure is a major feature that distinguishes the sixth group transition metal sulfide from other layered materials. Generally, the sixth group transition metal sulfide has three phase structures: 2H, 3R and 1T. Among them, 2H and 3R phases are semiconductor phases, while the 1T phase is metallic and has good conductivity. The results of literature research show that 1T-MoS with a 1T phase content of 70% 2 The conductivity of the large film is about 10-100 S / cm, which is higher than that of 2H-MoS 2 The conductivity of the large film is about seven orders of magnitude. In addition, 1T phase transition metal chalcogenides also show better performance than 2H phase and 3R phase chalcogenides in terms of electrochemical energy storage capacity (such as secondary ion batteries, supercapacitors, etc.), electrochemical catalytic activity (water decomposition reaction, carbon dioxide reduction reaction, nitrogen reduction reaction, etc.), electrochemical drive devices, surface Raman spectroscopy enhancement (SERS), superconductivity, etc. Therefore, the preparation of high-purity 1T phase structure transition metal chalcogenides has attracted widespread attention from researchers.

[0003] The most commonly reported method for preparing 1T-phase transition metal sulfide is to obtain it through chemical lithium insertion combined with liquid phase exfoliation process: that is, the parent layered 2H-phase transition metal sulfide powder is dispersed in a solution composed of butyl lithium and anhydrous n-hexane under an inert gas protective atmosphere, and the chemical lithium insertion reaction is carried out under stirring. After the reaction is completed, it is filtered and washed, and the product is dispersed in water or ethanol solvent, and liquid phase exfoliation is carried out under ultrasound assistance to obtain a dispersion of 1T-phase transition metal sulfide. In recent years, some other methods for preparing 1T-phase transition metal sulfide have also been reported in literature and patents, such as solid phase lithium insertion method, high temperature solid phase sintering method, hydrothermal method, etc. However, neither the most commonly used chemical lithium insertion method nor other preparation methods developed later can obtain pure 1T phase (100%) transition metal sulfide. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing pure 1T phase transition metal chalcogenides, which can not only obtain pure 1T phase (100%) transition metal chalcogenides, but also obtain transition metal chalcogenides with stable phase structure and large interlayer spacing.

[0005] Technical solution: The method for preparing pure 1T phase transition metal chalcogenide of the present invention comprises the following steps:

[0006] (1) adding a raw material for preparing a transition metal chalcogenide into N-methylformamide and stirring the mixture sufficiently to obtain a precursor solution;

[0007] (2) subjecting the precursor solution to a solvothermal reaction in a reactor; after the reaction is completed, washing and drying the obtained reaction product to obtain a pure 1T phase transition metal sulfide.

[0008] Wherein, in step (1), the transition metal chalcogenide is a transition metal sulfide or a transition metal selenide.

[0009] Wherein, the transition metal includes molybdenum or tungsten.

[0010] Wherein, when the transition metal chalcogenide is a transition metal sulfide, the raw material includes a molybdenum salt and an organic sulfur-containing compound; or the raw material includes a tungsten salt and an organic sulfur-containing compound.

[0011] Wherein, when the transition metal chalcogenide is a transition metal selenide, the raw materials include a selenium source, sodium borohydride and a molybdenum salt; or the raw materials include a selenium source, sodium borohydride and a tungsten salt.

[0012] Wherein, in step (1), the purity of the N-methylformamide is greater than 99%.

[0013] Wherein, in step (2), the temperature of the solvent thermal reaction is 160 to 280° C., and the reaction time is 10 to 120 hours.

[0014] Wherein, in step (2), the washing includes filtering or centrifuging; and the drying includes freeze drying or vacuum drying.

[0015] The method of the present invention is based on the principle of electron interaction in a chemical reaction process, and uses N-methylformamide with super-strong polarity and electron-donating ability as a solvent to carry out a solvothermal reaction. On the one hand, the method can perform in-situ electron injection on the reaction product (transition metal sulfide) during the reaction process to produce a pure 1T phase transition metal sulfide. At the same time, the layered 1T phase transition metal sulfide produced during the reaction process can be intercalated to expand its interlayer spacing and stabilize its 1T phase structure, thereby increasing its phase transition temperature for converting to a 2H form.

[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the method of the present invention uses N-methylformamide as a solvent for solvothermal reaction, which can not only produce pure 1T phase (100%) transition metal sulfide, but also the produced pure 1T phase transition metal sulfide has a large interlayer spacing (about 0.96 to 1.14 nanometers), which is conducive to the insertion / extraction of atoms, molecules or ions in certain physical / chemical reaction processes; thereby improving the structural stability of subsequent products in application scenarios such as catalysis, energy storage, and ion screening; at the same time, thanks to the internal electron enrichment and intercalation structure, the pure 1T phase transition metal sulfide produced by the present invention has excellent physical and chemical stability, and its 1T phase structure has good high temperature stability (no phase structure transformation occurs below 300°C). The present invention can provide 1T phase transition metal sulfide nanomaterials with high activity, high specific surface area, high stability, and enlarged interlayer spacing for many energy storage and energy conversion devices such as supercapacitors, ion batteries, and electro (photo) catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 1T-MoS prepared in Example 1 2 XRD pattern of

[0018] Figure 2 1T-MoS prepared in Example 1 2 Transmission electron microscope images of

[0019] Figure 3 1T-MoS prepared in Example 1 2 Spherical aberration electron microscope image;

[0020] Figure 4 1T-MoS prepared in Example 1 2 With 2H-MoS 2 XPS spectrum comparison;

[0021] Figure 5 1T-MoS prepared in Example 1 2 Differential scanning calorimetry curve of

[0022] Figure 6 1T-WS prepared in Example 2 2 XRD pattern of

[0023] Figure 7 1T-WS prepared in Example 2 2 Spherical aberration electron microscope image;

[0024] Figure 8 1T-MoSe prepared in Example 3 2 XRD pattern of

[0025] Fig. 9 1T-WSe prepared in Example 4 2 XRD pattern of . DETAILED DESCRIPTION

[0026] Example 1

[0027] The method for preparing pure 1T phase molybdenum sulfide nanopowder material of the present invention comprises the following steps:

[0028] (1) adding 236 mg of ammonium molybdate tetrahydrate and 508 mg of thiourea to 40 ml of N-methylformamide, and stirring at room temperature for 10 minutes to form a precursor solution;

[0029] (2) transferring the precursor solution to a polytetrafluoroethylene-lined autoclave, tightening the autoclave and placing it in a forced air drying oven for a solvothermal reaction at 160° C. for 120 hours;

[0030] (3) After the reaction is completed, the oven and the reactor are cooled naturally, and the inner shell of the reactor is taken out; the reaction product is poured out and washed by centrifugation with deionized water, and the solid matter after centrifugal washing is freeze-dried to obtain a pure 1T phase molybdenum sulfide nanopowder material.

[0031] Figure 1 The X-ray diffraction spectrum of the 1T phase molybdenum sulfide nanopowder material shows that the phase structure of the obtained powder material is 1T phase (without impurity phase) and the interlayer spacing is about 1.02 nanometers. Therefore, the present invention can prepare 1T phase transition metal chalcogenide with large interlayer spacing. Figure 2 This is a transmission electron microscope image of 1T phase molybdenum sulfide nanopowder material. The results show that the obtained powder presents a typical nanopowder morphology and has an obvious layered structure. Figure 3 This is a spherical aberration electron microscope image of 1T phase molybdenum sulfide nanopowder material. The results show that the obtained powder has a regular atomic arrangement, and the bright spots are molybdenum atoms. Due to the misalignment of the sulfur atoms in the upper and lower sandwich layers of the 1T phase structure, the contrast of the sulfur atoms cannot be observed, which also proves the pure 1T phase structure of the powder material. Figure 4 The 1T phase MoS nanopowder material is different from the commercially available 2H-MoS 2 The XPS spectra of the powder obtained in Example 1 were compared, and the results showed that the powder obtained in Example 1 had a 1T phase purity of 100%. Figure 5 This is the differential scanning calorimetry curve of the 1T phase molybdenum sulfide nanopowder material. The results show that the 1T phase structure of the obtained powder can exist stably at 300°C and below, and its 1T→2H phase transition temperature is about 350°C, indicating that the obtained 1T phase molybdenum sulfide nanopowder material has excellent thermal stability.

[0032] Example 2

[0033] The method for preparing the pure 1T phase tungsten sulfide nanopowder material of the present invention comprises the following steps:

[0034] (1) 594 mg of tungsten hexachloride and 751 mg of thioacetamide were added to 40 ml of N-methylformamide and stirred at room temperature for 15 minutes to form a precursor solution;

[0035] (2) transferring the precursor solution to a polytetrafluoroethylene-lined autoclave, tightening the autoclave and placing it in a forced air drying oven for solvothermal reaction at 240° C. for 24 hours;

[0036] (3) After the reaction is completed, the oven and the reactor are cooled naturally, and the inner container of the reactor is taken out; the reaction product is poured out and centrifuged with deionized water for washing, and then the solid matter after centrifugal washing is freeze-dried to obtain a pure 1T phase tungsten sulfide nanopowder material.

[0037] Figure 6 This is the X-ray diffraction spectrum of 1T phase tungsten sulfide nanopowder material. The results show that the phase structure of the obtained powder material is 1T phase (without impurity phase) and the interlayer spacing is about 0.96 nanometers. Figure 7 This is a spherical aberration electron microscope image of 1T phase tungsten sulfide nanopowder material. The results show that the obtained powder has a regular atomic arrangement, and the bright spots are tungsten atoms. Due to the misalignment of the sulfur atoms in the upper and lower sandwich layers of the 1T phase structure, the contrast of the sulfur atoms cannot be observed, which also proves the pure 1T phase structure of the powder material.

[0038] Example 3

[0039] The method for preparing pure 1T phase molybdenum selenide nanopowder material of the present invention comprises the following steps:

[0040] (1) 316 mg of selenium powder and 107 mg of sodium borohydride were added to 40 ml of N-methylformamide, and the mixture was stirred at room temperature for 20 minutes to form a mixed solution I; 484 mg of sodium molybdate dihydrate was further added to the mixed solution I, and the mixture was stirred for 5 minutes to form a mixed solution II;

[0041] (2) transferring the mixed solution II to a polytetrafluoroethylene-lined autoclave, tightening the autoclave and placing it in a forced air drying oven for solvothermal reaction at 200° C. for 24 hours;

[0042] (3) After the reaction is completed, the oven and the reactor are cooled naturally, and the inner shell of the reactor is taken out; the reaction product is poured out and washed by centrifugation with deionized water, and the solid matter after centrifugal washing is freeze-dried to obtain a pure 1T phase molybdenum selenide nanopowder material.

[0043] Figure 8This is the X-ray diffraction spectrum of 1T phase MoSe nanopowder material. The results show that the phase structure of the obtained powder material is 1T phase (without impurities) and the interlayer spacing is about 1.14 nanometers.

[0044] Example 4

[0045] The method for preparing the pure 1T phase tungsten selenide nanopowder material of the present invention comprises the following steps:

[0046] (1) 316 mg of selenium powder and 107 mg of sodium borohydride were added to 40 ml of N-methylformamide, and stirred at room temperature for 20 minutes to form a mixed solution I; 660 mg of sodium tungstate was further added to the mixed solution I, and stirring was continued for 5 minutes to form a mixed solution II;

[0047] (2) transferring the mixed solution II to a polytetrafluoroethylene-lined autoclave, tightening the autoclave and placing it in a forced air drying oven for solvothermal reaction at 280° C. for 10 hours;

[0048] (3) After the reaction is completed, the oven and the reactor are cooled naturally, and the inner container of the reactor is taken out; the reaction product is poured out and centrifuged and washed with deionized water, and the solid matter after centrifugal washing is freeze-dried to obtain a pure 1T phase tungsten selenide nanopowder material.

[0049] Fig. 9 This is the X-ray diffraction spectrum of 1T phase tungsten selenide nanopowder material. The results show that the phase structure of the obtained powder material is 1T phase (without impurity phase) and the interlayer spacing is about 1.03 nanometers.

[0050] Comparative Example 1

[0051] The preparation method of Comparative Example 1 is basically the same as that of Example 1, with the only difference being that the solvent in step (1) is 40 ml of N,N-dimethylformamide (DMF), and the phase structure of the obtained molybdenum sulfide nanopowder material is 2H phase with an interlayer spacing of 0.62 nm.

Claims

1. A method for preparing pure 1T phase transition metal chalcogenide, characterized in that: The steps include: (1) adding a raw material for preparing a transition metal chalcogenide into N-methylformamide and stirring the mixture sufficiently to obtain a precursor solution; (2) subjecting the precursor solution to a solvothermal reaction in a reaction vessel; After the reaction is completed, the obtained reaction product is washed and dried to obtain a pure 1T phase transition metal chalcogenide.

2. The preparation method according to claim 1, characterized in that: In step (1), the transition metal chalcogenide is a transition metal sulfide or a transition metal selenide.

3. The preparation method according to claim 2, characterized in that: The transition metal includes molybdenum or tungsten.

4. The preparation method according to claim 2, characterized in that: When the transition metal chalcogenide is a transition metal sulfide, the raw material includes a molybdenum salt and an organic sulfur-containing compound; or the raw material includes a tungsten salt and an organic sulfur-containing compound.

5. The preparation method according to claim 2, characterized in that: When the transition metal chalcogenide is a transition metal selenide, the raw materials include a selenium source, sodium borohydride and a molybdenum salt; or the raw materials include a selenium source, sodium borohydride and a tungsten salt.

6. The preparation method according to claim 1, characterized in that: In step (1), the purity of the N-methylformamide is greater than 99%.

7. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the solvent thermal reaction is 160 to 280° C., and the reaction time is 10 to 120 hours.

8. The preparation method according to claim 1, characterized in that: In step (2), the washing includes filtering or centrifuging; and the drying includes freeze drying or vacuum drying.